Kinesitherapeutic behaviour in conservative treatment of coxarthrosis - case report - Maria Becheva; Gergana Petrova; Angelina Kirkova; Petar Atanasov (Pensoft Publishers, 2019)
Hip arthrosis is the main cause of disability of all degenerative joint diseases and therefore it is considered to be of social significance. The presented clinical case aims to confirm the efficacy of the applied kinesitherapeutic program in conservative treatment of 62-year-old patient with right-sided coxarthrosis. The kinesitherapeutic methods included right lower limb massage, suspension therapy, tractions and manual movements of the right hip joint, positional treatment, active exercisesinan openkinetic chain, postisometric relaxation and stretching for shortened muscles. The pain symptoms were reduced, the volume of movement in the right hip increased, the strength of the right hip joint stabilizer muscles partially improved.